2018
DOI: 10.3389/fvets.2018.00212
|View full text |Cite
|
Sign up to set email alerts
|

Social Learning in Horses—Fact or Fiction?

Abstract: Prima facie, the acquisition of novel behaviors in animals through observation of conspecifics seems straightforward. There are, however, various mechanisms through which the behavior of animals can be altered from observing others. These mechanisms range from simple hard-wired contagious processes to genuine learning by observation, which differ fundamentally in cognitive complexity. They range from social facilitation and local enhancement to true social learning. The different learning mechanisms are the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…In the present study, horses failed to learn from observing humans in an instrumental task. This finding corresponds with the recent results from Burla et al [8] and Henriksson et al [9], who also found no effect of human demonstration on horses' success rate in a detour task, and moreover with the majority of the studies on intra-species social learning in horses (for a general review: Rørvang et al [4]). For example, Lindberg et al [19] and Ahrendt et al [20] found no effect of prior demonstration from a conspecific on the number of observer horses accomplishing an instrumental task, nor on their latency to do so.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, horses failed to learn from observing humans in an instrumental task. This finding corresponds with the recent results from Burla et al [8] and Henriksson et al [9], who also found no effect of human demonstration on horses' success rate in a detour task, and moreover with the majority of the studies on intra-species social learning in horses (for a general review: Rørvang et al [4]). For example, Lindberg et al [19] and Ahrendt et al [20] found no effect of prior demonstration from a conspecific on the number of observer horses accomplishing an instrumental task, nor on their latency to do so.…”
Section: Discussionsupporting
confidence: 91%
“…Individual learning refers to individual trial-and-error learning [2], whereas social learning has been used in the scientific literature to cover a wide range of learning mechanisms, ranging from simple processes to more cognitively complex processes [3]. As suggested by Rørvang et al [4], we distinguish between social transmission (social facilitation, stimulus enhancement, and local enhancement, i.e., the simpler processes), and actual social learning (goal emulation and imitation). Actual social learning requires higher cognitive abilities to learn about the goal and/or actions of the demonstrator.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another crucial part of social cognition involves social facilitation and/or learning [for a distinction see (83), from here on referred to as “social learning”]. These processes can occur through observational conditioning, local/stimulus enhancement, emulation and/or imitation (84).…”
Section: Introductionmentioning
confidence: 99%